The new public : - Mayhew, Leon H. (Cambridge University Press, 1997)
Professional specialists have come to dominate public communication, and the modern public of the Enlightenment been replaced by a "New Public", subject to mass persuasion through systematic advertising, lobbying, and other forms of media manipulation. Leon Mayhew examines this sociological development in terms of discourse and social influence, offering an original theory which bridges Talcott Parsons and Jurgen Habermas. He concludes that the present social order is unstable because good-faith, two-way discourse has been undermined.